Design and development of active vibration isolation system for free space optics communication - Turahim, Khairiah K.; Abdul Muthalif, Asan Gani; A. Rahim, Syazwani (Trans Tech Publications, Switzerland, 2012)
Free Space Optics (FSO) communication is a technology widely used today. It involves transmission of data from a transmitter to a receiver. In order to achieve successful data transmission, a continuous alignment between the transmitter and receiver telescope is needed. Misalignment could happen due to many factors. Vibration at the transmitter or the receiver is one of the factors that contribute to misalignment. In this work, active vibration isolation (AVI) system is designed and fabricated in order to improve the performance of the transmitter and receiver in an FSO link. First, a virtual prototype is designed. Then a real prototype is fabricated to implement AVI. The result after applying a controller to the AVI system shows 33.1% reduction in amplitude of displacement of the top plate, in other words reduction in amplitude of vibration.